The experiences of families regarding caring for family members who are terminally ill - Spies, Gloudien M. (University of Pretoria, 2018)
Caring for terminally ill patients can be regarded as an important public health concern in South Africa. In Sub-Saharan Africa, the Human Immunodeficiency Virus (HIV) or Acquired Immune Deficiency Syndrome (AIDS) and cancer are the most pressing concerns, with 22.5 million infected people in 2009, which means that two thirds (68%) of the global population is living with HIV/AIDS (Pool, 2011:10). It is generally known that South Africa is a leading country in Sub-Saharan Africa in the provision of palliative care. Previous research studies also revealed that many terminally ill patients are voicing the desire to die at home instead of in a hospital or in other health care institutions, which place an unbearable pressure on families. Family caregiving is generally provided by close family members of the terminally ill patient. Providing care to a family member with a terminal illness at home presents with several challenges, such as the fact that taking care of the terminally ill patient is time consuming, which may lead to feelings of social isolation. The goal of the research study was to explore the experiences of families regarding caring for family members who are terminally ill at home in the community of Ehlanzeni District in the Mpumalanga Province. The guiding research question was: What are the experiences of families regarding caring for family members who are terminally ill living in Ehlanzeni District in the Mpumalanga Province? A qualitative research approach was followed, with a collective case study as research design. The population for this study was family members who lived with a terminally ill patient. Non-probability, purposive sampling was applied to generate a sample. The sample size of the study was 11 participants between the ages of 18 and 62 years. Semi-structured interviews were used to collect the data, supported by an interview schedule to explore the experiences of family members regarding caring for terminally ill family members. All interviews were voice recorded with the consent of the participants. The data that was gathered by the researcher were analysed and themes and sub-themes were identified. The empirical findings of the study indicated that the physical demands of family caregiving for a family member with a terminal illness at home are often too much for families to handle on their own without the support of other professional systems. It also revealed that these caregivers, who are mostly females, often present with poor health themselves because of the pressure they experience during the caring process. Some of the family caregivers feel isolated, as they do not have enough time for themselves or for the other family members due to the fact that family caregiving demands almost all of their time. Some of these caregivers face financial constraints, their children‟s school performance decreases, and they are living in poverty-stricken conditions. Some of the participants indicated that family caregiving does have a positive side too, namely that they can take care of a family member, which is a symbol of love and respect. Conclusions and recommendations were formulated which focus primarily on the role of health professionals, including social workers, in providing a quality service to the terminally ill patients and their families. Themes for further research in this professional field were indicated.